1977
DOI: 10.1063/1.434544
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and phase transition in sodium azidea)

Abstract: Within the context of the quasiharmonic theory of lattice dynamics, the zone center frequencies, dispersion curves, and frequency distribution of sodium azide are calculated using two potential models. Good agreement is obtained between the calculated zone center frequencies and the available Raman data. In particular, the calculated temperature dependence of the splitting of the Eg librational mode in the β phase into Ag and Bg modes in the α phase is in excellent agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…As the schematic diagram shown in figure 4(b), compression leads to the shearing distortion of Na-layers parallel to ab plane and rotation of azide ions perpendicular to ab plane as the arrows shown, which, consequently, result in the structural phase transition from rhombohedral to monoclinic structure. The phase transformation mechanism was also well established in previous works about NaN 3 [26,30,31]. Additionally, the rotation process may also be accompanied with tilting of the azide ions.…”
Section: The Raman Spectra At High Pressuresupporting
confidence: 63%
See 1 more Smart Citation
“…As the schematic diagram shown in figure 4(b), compression leads to the shearing distortion of Na-layers parallel to ab plane and rotation of azide ions perpendicular to ab plane as the arrows shown, which, consequently, result in the structural phase transition from rhombohedral to monoclinic structure. The phase transformation mechanism was also well established in previous works about NaN 3 [26,30,31]. Additionally, the rotation process may also be accompanied with tilting of the azide ions.…”
Section: The Raman Spectra At High Pressuresupporting
confidence: 63%
“…During last century, a series of attempts have been conducted to exploring the stability, lattice dynamics, electronic structure, and optical properties of NaN 3 , while the pressure was restricted to 4.0 GPa [28]. As reported that application of pressure below 1.0 GPa or temperature near 20°C can initiate a phase transition from rhombohedral to monoclinic structure (α-NaN 3 ), accompanied by the shearing of the Na-layers and the tilting of the azide chains [14,25,26,[28][29][30][31]. Recently, Eremets et al revealed two pressure-induced phase transitions of NaN 3 at 19.0 and 50.0 GPa respectively [32].…”
Section: Introductionmentioning
confidence: 99%
“…In the temperatureinduced tetragonal-cubic phase transitions of both rubidium azide (RbN 3 ) and cesium azide (CsN 3 ), a fluctuation of the orientation of N 3 À anions was observed. [16][17][18] In both the temperature- 15 and pressure-induced [23][24][25] rhombohedral-monoclinic phase transition of sodium azide (NaN 3 ), a tilting of N 3 À anions was also observed. High-pressure studies on metal azides are of special interest recently because of their use as a precursor to form a highly energetic polymeric (non-molecular) form of nitrogen (N 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Metal azides undergo a variety of pressure or temperatureinduced phase transitions, a phenomenon which has been intensively studied. [14][15][16][17][18][19][20][21][22][23][24][25] The behavior of the azide anions (N 3 À ) during the phase transition is noticeable. In the temperatureinduced tetragonal-cubic phase transitions of both rubidium azide (RbN 3 ) and cesium azide (CsN 3 ), a fluctuation of the orientation of N 3 À anions was observed.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Previous studies indicated that inorganic azides undergo a variety of phase transitions, accompanied by the lattice distortion and reorientation of linear azide anions (N 3 À ) during the temperature or pressure induced phase transitions. [7][8][9][10][11][12][13] High-pressure study on inorganic azides has become an interest topic due to the polymerization of azide anions (N 3 À ) can form a high energy density material under high pressure. Polymerization of nitrogen net is pioneered by studies of nitrogen, a phenomenon which was first predicted in 1985 14 and recently achieved.…”
mentioning
confidence: 99%